THE EFFECTIVENESS OF GUIDED IMAGERY THERAPY ON PAIN INTENSITY IN POST SECTIO CAESARIA MOTHERS - Nunung Nurhayati; Selia Oktavianti; Astri Mutiar; Dewi Marfuah (Journal Of Midwifery And Nursing Studies, 2019)
The background : Pain is a problem that is often found in a patient post sectio of caesarea. It was caused by the presence of a stretch the muscles of the uterus and the abdomen after insisional on the network effect anasetesi missing. Pain management non pharmacological can be done by means of guided imagery. Guided imagery is one method of controlling pain are part of cognitive-behavioral. The purpose of this technique that is to provide comfort, change the psychology to reduce the perception of pain and optimalitation bodily functions. The purpose of evaluate the effectiveness guided imagery therapy against intensity of pain to post section of caesarea. Carried out search of articles on pubmed and google scholar. The search was expanded by using a technique citation pearl growing.Study published in english and indonesian language in 2010-2020 being considered to be included in the reviewed. The data extracted by writers and summarized use of p extraction data from JBI (Joanna Briggs Institute). Obtained 3 study entering review criteria. The guided imagery: Therapy effective to reduce pain post sectio of caesarea. Engineering guided imagery can be given 1 first hour of sectio caesarea post in a patient manner invited to imagine a nice thing, therapy guided imagery can be collected during 15-20 minutes a guided imagery therapy than other techniques of relaxation as to excite optimistic; increase confidence and relaxation and rest in deprive cycle, fear, tension pain; increase endorphin natural; and reduce fatigue the guided imagery therapy also do not need any fees, easy, by respondents and caused no side effects.